Mapping of cholera Priority Areas for Multisectoral Interventions (PAMIs) using the 2023 GTFCC guidance: The Kenya experience. - Catherine Kiama; Emmanuel Okunga; Catherine Makwe; Annastacia Muange; Martins Livinus; Daniel Langat; Joan Brunkard; Anne Loarec (PLoS Neglected Tropical Diseases)
Cholera Priority Areas for Multisectoral Interventions (PAMIs), formerly known as "hotspots", are limited geographical areas where cholera persists or regularly reappears due to cultural, environmental, and socioeconomic conditions. Focusing interventions on PAMIs will help to effectively control and ultimately eliminate cholera among the most at-risk populations. The 2023 GTFCC Methodology was used to identify PAMIs for cholera control in Kenya. The analysis was conducted between February and March 2024, selecting PAMIs based on the previous six years' epidemiological data (Jan 2018 - Dec 2023) at the sub-county level. Epidemiological data was sourced from cholera outbreak line lists. The line list included both confirmed and suspected cholera cases of all ages admitted or reported to health facilities. The numerical priority index was calculated as a sum of four epidemiological indicators: incidence, mortality, persistence, and laboratory testing. Following a validation workshop, stakeholders selected a priority index threshold, identifying 78 sub-counties as initial PAMIs. There were 29 additional PAMIs included in the final list of 107 priority sub-counties based on country-specific vulnerability factors. This evidence-based approach will inform the targeting and implementation of multi-sectoral interventions in line with the Kenya National Cholera Plan.